Regular physical exercise: way to healthy life - Siddiqui, NI; Nessa, A; Hossain, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):154-158 The abstract of this article is available on the PubMed website